Reasons for being: Storytelling the creation of a play about youth and mental health - Prendergast, Monica; Pauluth-Penner, Trudy (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2025)
This article reflects on an arts-based Social Science and Humanities Research Council funded study (2021-24), entitled ‘Youth mental health performance: How young people respond to portrayals of mental health, resilience, and well-being in and through drama and performance creation.’ Secondary theatre students as co-researcher artists from Riverside Secondary School in Coquitlam, BC were invited to explore how mental health was portrayed in Canadian Theatre for Young Audiences plays. Participants responded to these portrayals through play analysis workshops and collective theatre devising and performance. This paper highlights voices of the participants, making their thoughts and impressions the centrepiece of the paper. Methodology integrated ethnotheatre/drama, research-based theatre, and poetic inquiry processes. This study aligned with university and school district ethics protocols.